The relationship of mastery of Arabic language morphology to the speaking ability of students of the Darun Nun Sukun Islamic Boarding School Malang - Wafira, Naili Zulfa; Fikri, Shofil; Hermawan, M Khaerul (Abjadia : International Journal of Education, 2025)
Morphology is a branch of Arabic which studies the forms of words and their formation. This study aims to examine the relationship between the mastery of Arabic morphology and the speaking ability of students of Darun Nun Islamic Boarding School in Sukun Malang. This study uses mixed methods explanatory sequential design research method, because it wants to see the relationship of morphology to speaking ability, which is obtained from a combination of quantitative and qualitative data analysis. The sample consists of female students of the boarding school who are randomly selected with data collection in the form of a morphology mastery test and also a test of Arabic speaking ability. The results showed that the correlation coefficient between the mastery of Arabic morphology and speaking ability was calculated = 0.415, while rtabel = 0.456, this means that the two variables do not have a level of relationship. In the Sig. (2-tailed) of 0.077 > 0.05, then Ho is accepted and Ha is rejected, meaning that the hypothesis proposed by the researcher cannot be accepted, which means that there is no relationship, and significant between the mastery of Arabic morphology and the speaking ability of students of Darun Nun Islamic Boarding School Sukun Malang. There are other factors that support the ability to speak Arabic at the Darun Nun Islamic Boarding School, including the habituation of speaking Arabic in their daily lives and following the recitation of several books and mastery of vocabulary. Where all of this is supported by an Arabic-speaking environment which includes watching movies, listening to music, or reading news in Arabic so that it can improve language understanding and help in imitating intonation and speaking styles. An Arabic-speaking environment facilitates the natural language learning process, while book recitation activities help enrich vocabulary.